Breathe it in – Spotlight on senescence and regeneration in the lung. (October 2021) - Majewska, Julia; Krizhanovsky, Valery
Highlights: Senescence is a heterogenous cellular state with beneficial and detrimental roles. Extent of senescence-associated stress determines its program and function in vivo. Transient senescence aids regeneration to preserve functional integrity of a tissue. Chronic senescence is a driver of aging-related decline in organ function. Abstract: Cellular senescence, a highly coordinated and programmed cellular state, has a functional role in both lung physiology and pathology. While the contribution of senescent cells is recognized in the context of ageing and age-related pulmonary diseases, relatively less is known how cellular senescence of functionally distinct cell types leads to the progression of these pathologies. Recent advances in tools to track and isolate senescent cells from tissues, shed a light on the identity, behavior and function of senescent cells in vivo . The transient presence of senescent cells has an indispensable role in limiting lung damage and contributes to organ regenerative capacity upon acute stress insults. In contrast, persistent accumulation of senescent cells is a driver of age-related decline in organ function. Here, we discuss lung physiology and pathology as an example of seemingly contradictory role of senescence in structural and functional integrity of the tissue upon damage, and in age-related pulmonary diseases.